Temporal trends of the in vitro activity of tigecycline and comparator antibiotics against clinical aerobic bacterial isolates collected in Germany, 2006–2014: results of the Tigecycline Evaluation and Surveillance Trial (TEST) - Kresken, Michael (GMS Infect Dis, 2016)
Given the rapidly changing landscape of antimicrobial resistance, continuous monitoring of antimicrobial susceptibility in clinically relevant bacterial isolates plays an important role in the management of infectious diseases. The Tigecycline Evaluation and Surveillance Trial (TEST) is an ongoing worldwide surveillance programme monitoring the in vitro activity of tigecycline and a panel of representative comparator antibiotics. We report longitudinal susceptibility data on a large set of isolates (n=36,044) from clinically significant bacterial species collected in 25 microbiological laboratories from 2006 to 2014. Trends include a strong increase of carbapenem and levofloxacin resistance in Acinetobacter spp., and smaller increasing rates of ESBL-producing Escherichia coli and vancomycin-resistant enterococci. Across the reporting period, the tigecycline minimum inhibitory concentrations (MICs) at which 50% and 90% of isolates were inhibited remained stable and susceptibility rates were consistently high (93–100%) for all bacterial species.